Portfolio Diversification and Financial Performance of Microfinance Institutions in Nairobi County, Kenya - Nyabiba, Jully Kemunto; Kimani, E. Maina (International Journal of Finance, 2023)
Purpose: The current study sought to establish the effect of portfolio diversification on financial performance of microfinance institutions in Kenya. The study focused on establishing the effects of asset class diversification, risk profiling diversification, income diversification and locational diversification on performance of microfinance institutions in Kenya. The study was supported by Shiftability Theory, Capital Market Theory, Resource Based Theory and Balanced Score Card Theory. Methodology: A descriptive research design was used and targeted 57 micro finance institutions operating in Nairobi County and registered under Association of Micro Finance Institutions. The unit of observation comprised of employees in top level management including chief financial officer, operational manager, and chief manager making a total of 171 respondents. The study employed a census approach. Both primary and secondary data were utilized in the study. Primary data was gathered using a five point Likert scale questionnaire while a secondary data collection sheet was utilized to collect secondary data from financial reports of the respective institutions. Both descriptive and inferential statistics was used to analyze the collected data. The statistics were generated through Statistical Package for Social Scientists and MS Excel. Findings: The results were displayed in form of tables. The study established that portfolio diversification comprising of asset class, risk profiling, and income diversification positively and significantly affect financial performance of the MFIs operating in Nairobi County as shown by respective beta values of 0.318, 0.288 and 0.498 and significant values of 0.000, 0.005 and 0.000. This bears the implications that enhancing aspects of each of the portfolio diversification contributes to improved financial performance of the institutions. Locational diversification on the other had had a positive but insignificant effect on financial performance of the MFIs (beta=0.103, sig=0.000>0.05) which implies that enhancing aspects of locational diversification contributes insignificantly to financial performance of the MFIs. Unique contribution to theory, practice and policy: The study provided recommendations to the management of the MFIs to enhance the levels of asset class diversification, risk profiling diversification, and income diversification since the practices bears positive and significant effect on financial performances of the MFIs.